The Role of Witness as Evidence in Divorce Cases at the Banda Aceh Syar’iyah Court - Devy, Soraya; Bahri, Syamsul; Ariga, Selamat; Aslam Ahmad, Muhammad; Buchary Budiman, Mumtazinur; Sri Wahyuni, Yenny (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This study examines the role of witnesses as evidence in a divorce case at the Banda Aceh Syari’iyah Court. This study aims to determine the legal basis of witnesses as evidence, the background of the witnesses who were submitted due to disputes or syiqaqand the position of female witnesses in divorce cases. This study uses empirical legal research or sociological law, which is a study whose object is legal phenomena using sociological theories. The legal phenomenon in question is the application of law at the Banda Aceh Syar’iyah Court, particularly regarding witness evidence in divorce cases. Data collection techniques were carried out by means of in-depth interviews with judges and literature studies related to the existence of witnesses and judges’ decisions as primary data related to witnesses as evidence. This study concludes that witnesses as evidence are based on the Qur’an and hadithand the applicable laws and regulations. Witnesses have existence as evidence used by judges as a consideration in deciding cases. In the case of a divorce caused by a dispute, the witness evidence comes from the close family background of the husband or wife. Close family who really know, see and hear the events that occur in their household. In civil procedural law for divorce cases at the Syar'iyah Court, women have the same and equal position as men in giving testimony. The testimony of close families and the sociological equality of women and men is a legal fact that must be appreciated to achieve justice for all parties.